Solvent Selection for Mitragynine Extraction by Hansen Solubility Parameter - Ditthapornset, Sirawich; Lerkkasemsan, Nuttapol; Areerat, Surat (My University, 2023)
Mitragyna speciosa (Korth.) Havil., commonly known as “Kratom” has a wide range of therapeutic benefits. In this research study the solvents that can be used to extract Mitragynine from kratom leaves. To predict solubility parameters, Hansen solubility parameters were employed. Then analyzing the solubility parameters using the ProCAPE application However, Mitragynine cannot directly determine the solubility. Instead, a method for evaluating the solubility from derivatives of Mitragynine was used in this study. A ternary graph shows the solubility of the derivatives and solvents. The solvents selected were considered for safety from the GSK’s Solvent Selection Guide. From the results, it was found that several types of solvents which that were dissolved derivatives of Mitragynine better than conventional solvents. Additionally, while using ProCAPE, the solubility parameters were predicted from extraction-related research was applied, and the results were shown as ternary graphs. The graphs were confirmed to be in accordance with the experimental data from the research that was collected.
Keywords: GSK’s Solvent Selection Guide; Kratom; Mitragynine; ProCAPE; Solubility Parameter